Eviscerating a Healthy Church-State Separation - Erwin Chemerinsky; Barry P. McDonald (Washington University Law Review, 2019)
In its recent ruling in Trinity Lutheran Church of Columbia, Inc. v. Comer, the U.S. Supreme Court took an extraordinary step in a remarkably facile way. For the first time in its history, the Court ruled that the United States Constitution requires states under certain circumstances to provide taxpayer funds to churches and other houses of worship. The Court relied on the Free Exercise Clause of the Constitution to force the State of Missouri to provide funding to a church in contravention of an anti-establishment clause contained in that State’s own constitution. Why an extraordinary step? Because deeply ingrained in the history of American religious freedom is a fight against coerced taxpayer funding of religious communities to protect rights of religious conscience and a healthy separation of church and state. This no-funding principle was reflected in many of the constitutions of the original states, in the federal Free Exercise and Establishment Clauses as they came to be understood soon after adoption, and in provisions of most state constitutions adopted later in the nineteenth century that remain in place today. This Article will elaborate on these themes and proceed in the following way. Part I reviews the historical understanding of free exercise rights, and anti-establishment provisions that were adopted mainly to buttress those rights. It demonstrates how both sets of protections came early on to be understood as containing a ban on the use of taxpayer funds to support churches and other houses of worship in order to safeguard, among other things, the right of individuals not to be coerced into promoting religious beliefs they could not in good conscience support. It then discusses how the Court’s decision in Trinity Lutheran plays somersaults with this history, and substantially undermines it despite the conservatives’ frequent defenses of using historical understandings to interpret the Constitution in other areas. Part II turns to precedent and argues that the Court’s application of its earlier decisions in Trinity Lutheran was not faithful to them. Part III then argues that despite the seemingly innocuous results in the Trinity Lutheran dispute itself, the Court’s decision will have far-reaching and undesirable consequences for protecting freedom of religious conscience and a healthy separation of church and state in this country. Next, Part IV contends that there are compelling historical, legal and normative reasons for treating the public funding of religious institutions differently than secular ones. Lastly, Part V demonstrates how Trinity Lutheran is the most recent in a trend of decisions by the conservative wing of the Rehnquist and Roberts Courts to lower the church-state wall in a misguided way, one that will only be accelerated by the recent appointments of Justices Neil Gorsuch and Brett Kavanaugh to the Court—giving the conservatives a solid five-vote majority for years to come.
Keywords: Trinity Lutheran Church of Columbia v. Comer; Church-State separation; Constitutional law; Free exercise clause; Separation of church and state; Establishment clause; First amendment; Religious institutions